Smart partnerships in education: what are they? - Davis, Niki; Leahy, Margaret; Charania, Amina; Nordin, Hasniza; Orlic, Davor; Lewin, Cathy; Lopez-Fernandez, Olatz (2016)
This paper which arises from EDUsummIT 2015 provides an overview of the development of a working definition of Smart Partnerships (SP) in education before describing and analysing three potential SPs of which only one is identified as a SP.Further research and development of SPs are recommended to further understand SPs and to unleash the potential of digital technologies in education.